Pelatihan Terapi Endrorphine Massage Pada Ibu Hamil Tm 3 Primigravida Di Rumah Sakit Dr. Sobirin Lubuk Linggau - Danur Azissah; Handi Rustandi; Jipri Suyanto; Mira Damayanti; Emi Pebriani (Universitas Dehasen Bengkulu, 2024)
Universities are the pioneers in organizing the higher education process. A reliable Tri Dharma of Higher Education is the relationship between higher education and society that is established in a hamonis and mutual need. The existence of community service is actually very important for university managers and for the existence of the university itself. In order to carry out the Tri Dharma of Higher Education, the Faculty of Health Sciences, Dehesen University Bengkulu organizes an increase in health knowledge to the community, one of which is community service carried out is